MATEC Web of Conferences - Korotkikh, A. G. specialist in the field of power engineering Professor of Tomsk Polytechnic University, Doctor of Physical and Mathematical Sciences 1976- (EDP Sciences, 2018)
Boron and its compounds are among the most promising metal fuel components to be used in solid propellants for solid fuel rocket engine and ramjet engine. Papers studying boron oxidation mostly focus on two areas: oxidation of single particles and powders of boron, as well as boron-containing composite solid propellants. This paper presents the results of an experimental study of the ignition and combustion of the high-energy material samples based on ammonium perchlorate, ammonium nitrate, and an energetic combustible binder. Powders of aluminum, amorphous boron and aluminum diboride, obtained by the SHS method, were used as the metallic fuels. It was found that the use of aluminum diboride in the solid propellant composition makes it possible to reduce the ignition delay time by 1.7-2.2 times and significantly increase the burning rate of the sample (by 4.8 times) as compared to the solid propellant containing aluminum powder. The use of amorphous boron in the solid propellant composition leads to a decrease in the ignition delay time of the sample by a factor of 2.2-2.8 due to high chemical activity and a difference in the oxidation mechanism of boron particles. The burning rate of this sample does not increase significantly.